Materials science and engineering : an introduction - Callister, William D., 1940- (Hoboken : John Wiley, 2003)
Presents eight learning modules on materials science and engineering concepts. Includes online self-assessment and features three-dimensional projections and animations.
Title from disc label.
'Student learning resources'.
Book is accompanied by one CD, entitled'Student learning resources - Materials science and engineering : an introduction' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references and index.
System requirements: IBM-compatible PC; 16MB RAM (64MB RAM for Windows NT 4.0); Windows 95 or higher; 10MB free hard disk space; 256-color SVGA monitor and video card; sound card; 4X CD-ROM.
Keywords: Materials